Costs and Benefits of Vegetable Gardening - Kevin Athearn; Hannah Wooten; Liz Felter; Catherine G. Campbell; Jessica E. Ryals; Matthew C. Lollar; Juanita Popenoe; Lorna Bravo; LuAnn Duncan; Christa Court; Wendy Wilber (EDIS)
Home vegetable gardening has numerous documented benefits, including savings on the family food bill. How can a gardener calculate cost savings from a garden? Which vegetables cost more to grow in the garden and which cost less? This 10-page fact sheet written by Kevin Athearn, Hannah Wooten, Liz Felter, Catherine G. Campbell, Jessica M. Ryals, Matthew C. Lollar, Juanita Popenoe, Lorna Bravo, LuAnn Duncan, Christa Court, and Wendy Wilber and published by the UF/IFAS Food and Resource Economics Department helps home gardeners estimate the costs and cost savings from vegetable gardening